English Acquisition of Reading and Writing Skills on Learners at Fourth Grade at Jesus School - Calderón Mora, Roxy (Universidad Estatal a Distancia, 2014)
Teaching English in II Cycle at public primary schools in Costa Rica relies on integrating and interrelating the four basic skills in the communication process.  The English Acquisition of Reading and Writing Skills on Learners at fourth grade at Jesus School article is a consolidation of the research study developed in 2013.  The purpose of this study was to research on learning strategies that stimulate the acquisition of reading and writing skills in fourth level at Jesus de Atenas public school located in Atenas. The study implemented reading and writing strategies.  The collection of data was performed by using a qualitative approach using four different instruments: three classroom observations, two artifacts as evidence of the students’ performance, a focus group and, an interview to the English advisor at Regional de Alajuela. The data collection process demonstrated that students improved both reading and writing competence after performing strategies such as Word Walls, Group Writing and Print- Rich Environment.  The analyzed results in this study confirmed that the applied strategies stimulate the acquisition of reading and writing skills in fourth graders at a public school.